Introduction - Jean-Claude Yon (In Situ)
Written by a historian of the performing arts who once worked at the Musée d'Orsay, this introduction aims to put the fifteen or so texts in this dossier into perspective. To do this, after a reminder of the specific features of theatre heritage, the reflection unfolds in two stages. Firstly, emphasis is placed on the extraordinary variety of these heritages, within which three major groupings can be distinguished: 'technical and craft knowledge', archives, audiovisual and digital. Secondly, four uses for this heritage are highlighted: serving as sources for researchers, introducing the general public to theatre, contributing to a region's identity, and serving as material for creative artists. The introduction concludes with a statement of five priorities that should help to make better use of these heritages, which are formidable tools for understanding our societies and societies of the past.